Closer to people and trees: will decentralisation work for the people and the forests of Indonesia? - Resosudarmo, I.A.P. (2004)
For over 30 years, Indonesia's central government controlled its forests, the third largest area of tropical forests in the world. Driven by serious political, administrative, and economic demands for reforms, the central government has begun to decentralize, transferring new powers to the district and municipal levels. Decentralization in the forestry sector has included transferring income from permits, logging and reforestation fees, as well as the right for these lower levels of government to issue logging permits. This sudden, new access to Indonesia's lucrative timber market has led local peoples and governments to rush to take advantage of a resource to which they previously had little right. The result has included the proliferation of permits with little regard for the effect on forest resources. Large areas, including some protected areas, are being destroyed and threatened with conversion to other uses. Local peoples, however, appear not to have been the ones receiving the primary benefits; they have been taken instead by those who have the required capital for permits and logging.